1993
DOI: 10.1525/ap3a.1993.4.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Function among Gravette Points from Southwestern France

Abstract: A number of morphological and metric variables were recorded for a sample of 1,451 Gravette points deriving from ten sites in southwestern France. Size, macrowear, and base treatment covaried in a manner suggesting that some Gravette "points" in fact functioned as knives. The sample artifacts, however, did not segregate neatly into two distinct morphological-functional types of knives and points, but rather formed a continuum from more knife-like to more point-like pieces. Some probably functioned in both ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Lithic blades of these dimensions are ubiquitous in MUP assemblages (e.g. Otte, 1979; Harrold, 1993; Straus, 2002; Conard & Moreau, 2004; Otte et al ., 2006; Svoboda, 2007; Borgia, 2008; Nuzhnyi, 2009; Svoboda et al ., 2009), including on the Russian Plain (Vishnyatsky & Nehoroshev, 2004) and at Sunghir (Bader, 1978, 1998). In particular, one of the lithic points directly associated with the Sunghir 1 burial, found between the feet (Bader, 1998), would make a reasonable match for the injury to the thoracic vertebra, except that its thickness (∼3.5 mm, 6–7 mm from the tip, from the illustration in Bader (1998)) exceeds the width of the incision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithic blades of these dimensions are ubiquitous in MUP assemblages (e.g. Otte, 1979; Harrold, 1993; Straus, 2002; Conard & Moreau, 2004; Otte et al ., 2006; Svoboda, 2007; Borgia, 2008; Nuzhnyi, 2009; Svoboda et al ., 2009), including on the Russian Plain (Vishnyatsky & Nehoroshev, 2004) and at Sunghir (Bader, 1978, 1998). In particular, one of the lithic points directly associated with the Sunghir 1 burial, found between the feet (Bader, 1998), would make a reasonable match for the injury to the thoracic vertebra, except that its thickness (∼3.5 mm, 6–7 mm from the tip, from the illustration in Bader (1998)) exceeds the width of the incision.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of these pointed blades were hafted onto armatures for spears and probably other implements in the MUP (Harrold, 1993; Straus, 2002; Shea, 2006). There may have been spear throwers given the dimensions of some of the available points ( cf ., Shea, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The Gravettian lithic record is characterised by the presence of distinct artefacts with morphologies suggestive of projectile function, including tanged points, Gravette and microgravette points, and fléchettes. Projectile use has been confirmed for some of them through usewear studies relying on tailored experimental reference material [14,57,58], but other functional analyses have demonstrated that not all pointed objects functioned as armatures [59][60][61][62].…”
Section: Gravettian Hunting Weaponry In Contextmentioning
confidence: 99%
“…Backed tools, which include Gravette points, microgravette points, and backed bladelets, are among the type fossils of Gravettian industries, and form an important component of the Level 3 and 2 assemblages [see 85]. In other contexts, these items have been classically perceived as projectile armatures although knife function has sometimes been proposed for some of them [59][60][61]69] and also use in craft activities has been reported [69]. The shift from Gravette and microgravette points to truncated backed pieces has been viewed as the replacement of distally hafted weapons tips by laterally hafted ones towards the end of the Gravettian [6].…”
Section: Lithic Assemblage and Backed Toolsmentioning
confidence: 99%
“…In the later European Upper Palaeolithic different types of backed points characterize several technocomplexes, e.g. Gravettian, Azilian and Creswellian (Sonneville- Bordes, 1960;Harrold, 1993). Also, across the African Stone Age specific backed pieces define several entities, e.g.…”
Section: Mousterianechâtelperronian Links: Continuity or Rupture?mentioning
confidence: 99%